INHIBITION OF PATHOGENS BY LACTIC ACID BACTERIA AND APPLICATION AS WATER ADDITIVE MULTI ISOLATES IN EARLY STAGES LARVICULTURE OF P. PELAGICUS (LINNAEUS, 1758) - A. D. Talpur; A. J. Memon; M. I .Khan; M. Ikhwanuddin; M. M. Danish; Daniel; A.B Abol-Munafi (Journal of Animal and Plant Sciences, 2012)
In aquaculture practices, to date, probiotics are considered a valid alternative to antibiotics and in particular, in fish larviculture, to prevent high mortality. Looking for innovative ways, Lactic Acid Bacteria (LAB) were isolated from the gut of female P. pelagicus and tested as water additive mixture in the P. pelagicus larviculture to determine their effects on survival, water quality, and enzymatic activity. The LAB mixture was added to the culture water daily at 1x106, 5x106 and 1x107 cfu mL-1. Control group did not receive any bacteria. All trials were replicated. Probiotic addition improved larval survival significantly in all the trials. Higher larval survival averaged 10.3%, 11.2% and 11.0% respectively was achieved in treatment groups inoculated with a mixture of three LAB including L. plantarum, L. salivarius and L. rhamnosus. The isolates also lowered pH and increased digestive enzyme activity particularly protease and amylase compared to that of control. The data collected provided scientific and technical support for the utilization of probiotics larval rearing of P. pelagicus for sustainable culture of this crab species in specific and aquaculture in general.
Keywords: P. pelagicus; Lactic Acid Bacteria; Larviculture; Digestive enzyme.